Effects of Recreational Football on Bone Mineral Density and Isokinetic Muscle Strength in Elderly Men: A Study of Turkish Older Men - Cemal Polat; Alparslan Unveren; Hayri Ertan; Gian Mario Migliaccio; Zarife Pancar; Luca Russo (Medicina)
Background and Objectives: Recreational football (RF) as a community activity can provide a positive transformative effect on the musculoskeletal systems necessary for the self-care and independent life demands of older adults when designed with a geriatric approach, in addition to its psycho-social benefits. However, studies investigating the potential value of these practices in older adults living in different ecosystems are needed. The aim of this study was to investigate the effects of RF on bone mineral density (BMD) and knee isokinetic muscle strength (KIMS) at angular velocities of 60°/s−1 and 120°/s−1 in older adult men. Material and Methods: A total of 57 elderly men (65.5 ± 2.7 years) were randomly divided into a football group (FG; n = 28) and a control group (CG; n = 29). The FG participated in 28 sessions of training, twice a week. Participants were evaluated using the DEXA and IsoMed 2000. The groups, their pre-test–post-test time differences, and group*time interactions were analyzed by mixed design ANOVA. Results: The results were analyzed considering a p < 0.05 significance level. There was no observed statistically significant difference between the groups for bone mineral density values (p > 0.078), but there was an observed statistically significant difference in the FG group*time interaction (F = 7.009, p < 0.009, η2p = 0.060). There was a statistically significant difference between the groups in the peak torque flexion and peak torque extension values at 60°/s−1 angular velocity, respectively (p < 0.002, p < 0.011). At 120°/s−1 angular velocity, peak torque flexion and extension, total work flexion and extension, and peak power flexion and extension showed statistically significant differences between the groups, respectively (p < 0.001, p < 0.0027; p < 0.003, p < 0.025; p < 0.001, p < 0.009). Conclusions: These results suggest that RF interventions provide positive biochemical and morphological adaptations in bone mineral density and lower extremity muscle groups, making older adults both more resistant to potential risks and encouraging exercise as a way of life with its autotelic flow structure.